2012
DOI: 10.1371/journal.pone.0050453
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of Activity Based Anorexia Susceptibility in Diverse Genetic Rodent Populations

Abstract: Animal studies are very useful in detection of early disease indicators and in unravelling the pathophysiological processes underlying core psychiatric disorder phenotypes. Early indicators are critical for preventive and efficient treatment of progressive psychiatric disorders like anorexia nervosa. Comparable to physical hyperactivity observed in anorexia nervosa patients, in the activity-based anorexia rodent model, mice and rats express paradoxical high voluntary wheel running activity levels when food res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…The best predictive model was a combination of RW activity during ad-libitum feeding, SPA and body weight history (Figures 4 and 5). Previous studies of ABA susceptibility showed that RW activity is a strong predictor of body weight loss during ABA in female rats [18, 25, 26]. Our results add support to the hypothesis that RW activity during ad-libitum feeding has predictive value for body weight changes during ABA in female rats and extend this result to male rats (Figure 4 and 5).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The best predictive model was a combination of RW activity during ad-libitum feeding, SPA and body weight history (Figures 4 and 5). Previous studies of ABA susceptibility showed that RW activity is a strong predictor of body weight loss during ABA in female rats [18, 25, 26]. Our results add support to the hypothesis that RW activity during ad-libitum feeding has predictive value for body weight changes during ABA in female rats and extend this result to male rats (Figure 4 and 5).…”
Section: Discussionsupporting
confidence: 90%
“…All these parameters, except SPA and stereotypic behavior, have been suggested to predict severity of weight loss during ABA in other studies [25-27]. …”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this paradigm, when food access is restricted in the presence of a running wheel, animals paradoxically increase their exercise, consume less food than sedentary controls and lose more weight, running themselves to death within a few weeks. There is individual vulnerability in susceptibility to ABA, but young female rats with higher activity levels at baseline tend to eat the least, run the most, and lose the most weight [68][69][70], consistent with the clinical observation in AN that excessive exercise often precedes dieting and escalates with weight loss [71,72]. Excessive exercise has long been recognized as a hallmark of AN [73], is present in up to 80% of cases and appears to play a central role in the pathogenesis and progression of the disorder [74].…”
Section: Learning Habit Formation Stress and Fear Conditioning: Relmentioning
confidence: 99%